ANALISIS PELAKSANAAN FULL DAY SCHOOL DI SMK NEGERI 1 PONTIANAK - Amelia, Endah Luthfatul; Ulfah, Maria; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to find out how the implementation of full-day shool program at SMKN 1 Pontianak. The research method used was descriptive study in a form of qualitative. The subject of this research included the headmaster, teachers, and the students of SMKN 1 Pontianak, and the datawere sheets of observation, result of interview, and documentation. The researcher used domain data of analysis and degree data of credibility. The result of this research showed that the implementation of full-day school program at SMKN 1 pontianak has been in optimalized utilation of time as big as 4,75 which was categorized assubstantial, improving and discovering talent was 3,4 was categorized as moderate, embeding the improtance of process as big was 3,7 categorized as moderate, the students' focus and learning were 2,7 categorized as low, in expanding the creativitywas 3 categorized as moderate, and students were being controlled well was 3,4 that was categirized as moderate. Keyword: Implementation, Full day school program